2015
DOI: 10.3109/01676830.2015.1022661
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Decompression for the Treatment of Spontaneous Globe Luxations

Abstract: Orbital decompression is an effective method for the prevention of new episodes in patients with spontaneous globe luxations. It has good aesthetic and functional results and addresses the exophthalmos present in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…1 Though infrequently reported, exophthalmos secondary to orbital fat hypertrophy is also noted as a predisposing factor in obese patients. 7 SGL can be caused by non-traumatic eye manipulations, as in the case presented. It can also be caused by forceful Valsalva or eyelid maneuvering during contact lens insertion, as users push the eyelids past their natural threshold.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…1 Though infrequently reported, exophthalmos secondary to orbital fat hypertrophy is also noted as a predisposing factor in obese patients. 7 SGL can be caused by non-traumatic eye manipulations, as in the case presented. It can also be caused by forceful Valsalva or eyelid maneuvering during contact lens insertion, as users push the eyelids past their natural threshold.…”
Section: Discussionmentioning
confidence: 69%
“…3,26 Obesity is an important risk factor that causes exophthalmos and is also associated in with FES in patients. 7,13,26 However, other reports have also shown that FES could occur in individuals with normal BMI. 27 In the case presented, the patient was African American and obese.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations